If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + -45 = 4t Reorder the terms: -45 + 9t = 4t Solving -45 + 9t = 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. -45 + 9t + -4t = 4t + -4t Combine like terms: 9t + -4t = 5t -45 + 5t = 4t + -4t Combine like terms: 4t + -4t = 0 -45 + 5t = 0 Add '45' to each side of the equation. -45 + 45 + 5t = 0 + 45 Combine like terms: -45 + 45 = 0 0 + 5t = 0 + 45 5t = 0 + 45 Combine like terms: 0 + 45 = 45 5t = 45 Divide each side by '5'. t = 9 Simplifying t = 9
| 18h-17h= | | 4(x+3)-3=2(4-3x-4) | | X+8+x+5=9 | | X+(X*0.085)=5000 | | 8s+17s=125 | | 2(7-3n)=14+6n | | √-80/√-10 | | 2[3x-5]=8 | | 87-x=52 | | -80/-10 | | 2ln(22x+1)=8 | | 5-(4-2x)2/3=1 | | 3/4*7/8-1/2 | | -1w-2=26 | | u+-7=8 | | x*4/3x=192 | | 5/6-1/3*5/8 | | (1+4x)(1-2x)= | | 6x+8-2x=-12 | | 10x+2x-8x=-28 | | 5z-7=3z+5 | | 2t^0/2t^-1 | | 9w-3-16w+8=6-6w-24 | | 21y=0 | | 10-6x=4x-10 | | 5/6*1/4-1/8 | | 14x-11+90=20x+55 | | 9s-12+2s=64 | | 5x+5x+2=22 | | 0.57x=8 | | 5n-30=4n | | -2x+15=43 |